Aurantiacibacter sediminis sp. nov., a marine bacterium isolated from a tidal flat. Issue 6 (6th June 2022) - Kim, Chul-Hwan; Yoo, Yeonjae; Kim, Dongjun; Khim, Jong Seong; Pathiraja, Duleepa; Kim, Bogun; Choi, In-Geol; Kim, Jae-Jin
Abstract : A yellow-coloured bacterium, designated as strain JGD-13 T, was isolated from a tidal flat in the Republic of Korea. Cells were Gram-stain-negative, aerobic, non-flagellated and rod-shaped. Growth was observed at 4–42 °C (optimum, 30 °C), at pH 6.0–12.0 (pH 7.0–8.0) and at 1–7 % (w/v) NaCl concentration (3 %). The 16S rRNA gene sequence analysis indicated that strain JGD-13 T was closely related to Aurantiacibacter gangjinensis K7-2 T with a sequence similarity of 98.2 %, followed by Aurantiacibacter aquimixticola JSSK-14 T (98.1 %), Aurantiacibacter atlanticus s21-N3 T (97.6 %), Aurantiacibacter zhengii V18 T (97.6 %) and Aurantiacibacter luteus KA37 T (97.5 %). The average nucleotide identity and digital DNA–DNA hybridization values with related strains were 70.3–76.2 % and 18.5–20.3 %. The genomic DNA G+C content was 60.2 mol%. Phylogenetic analysis using the maximum-likelihood method showed that strain JGD-13 T formed a clade with A. aquimixticola JSSK-14 T and A. gangjinensis K7-2 T . The major fatty acids were summed feature 8 (39.7 %) and C17 : 1 ω 6 c (14.4 %). The predominant respiratory quinone was ubiquinone-10. The polar lipids were phosphatidylethanolamine, phosphatidylglycerol, phosphatidylcholine, one sphingoglycolipid and three unidentified lipids. On the basis of phylogenetic, phenotypic and chemotaxonomic characteristics, strain JGD-13 T represents a novel species within the genus Aurantiacibacter, for which the name Aurantiacibacter sediminis JGD-13 T sp. nov. is proposed. The type strain is JGD-13 T (=KCTC 72892 T =KACC 21676 T =JCM 33995 T ).